Optimizing Land and Building Fixed Asset Management: Review of Legal Audit, Control and Supervision - Siti Hasanah; Entis Sutisna (Faculty of Business and Economics , Universitas Yapis Papua, 2023)
Regional asset management is one of the keys to successful regional economic management. The importance of managing assets appropriately and effectively, based on the principles of efficient and effective management, is expected to be able to give strength to Regional Governments to finance regional development. This research aims to determine the influence of legal audits and control and supervision on optimizing fixed asset management. The population in this study were employees. The sampling in this research was a non-probability sampling design with judgment sampling techniques obtained using instruments in the form of 97 questionnaires. The data analysis method in this research used Structural Equation Model (SEM)-PLS analysis with the help of Smart-PLS software. Research results show that legal audits as well as control and supervision can influence the optimization of land and building fixed asset management. These two variables can explain the optimization of land and building fixed asset management by 35.3% .